Performance of a Solar Seawater Distillation with a Triangle Prism Cover and a Fin-Type Absorber - Rachmanita, Risse Entikaria; Umam, Miftah Khoirul (Makara Journal of Technology, 2023)
Solar-powered distillation is a seawater distillation method that utilizes solar heat as its main energy source for the purpose producing freshwater and a by-product of the distillation process in the form of salt. This study aims to determine the performance of a solar seawater distillation design with a semi-batch system by combining a fin-type absorber plate and a triangular prism cover. This design is equipped with a reflector and absorber plate, which has a surface area of 0.3969 m2 with a volume capacity of seawater that can be accommodated in a basin of ±24 liters. It uses a knockdown system on its components for convenience in the process of maintenance and repair. The test results show that the highest freshwater product produced is 0.245 liters and the quality of distilled water meets the standards for consumption. The highest efficiency of solar seawater distillation test results was 8.032% on the third day of testing with an average solar radiation intensity of 805.076 W/m2 . The efficiency of solar distillation of seawater is strongly influenced by the intensity of solar radiation received by the distillation apparatus.